Herding Ecologies and Ongoing Plant Domestication Processes in the Americas - Lezama-Núñez, Paulina R.; Santos-Fita, Dídac; Vallejo, José R. (Frontiers in Plant Science, 2018)
Understanding both domestication processes and agricultural practices is an interdisciplinary endeavor. Ethnographic research is potentially helpful for reconstructing past events. Such knowledge is also crucial for documenting the links between biological and cultural diversity, as well as for future purposes such as innovation in food production and sustainability. Here, we review six ethnographic case studies in different pastoral socioecological systems of the American continent. The livestock species involved include the native South American camelids and Arctic reindeer, as well as some Old World species (mainly goats, sheep, and cattle). Starting with the Columbian exchange (15th-16th centuries) and continuing up to the present, Old World herbivores launched novel uses of the local flora which resulted in entirely new livelihoods and cultures, i.e., pastoralism with its variants. Three of these case studies approach specifically how herding ecologies (human–animal–plant relationships) stirred specific management practices (human–plant relationships) that in some instances have moved toward conscious human selection of plant phenotypes. The other examples correspond to three potential instances of similar ongoing processes that we propose on the basis of ethnobotanical and ethnozoological data that were produced separately by other authors. Based on the studies we have reviewed, along with additional information from other parts of the world, we are able to conclude that: (a) New World pastoralist societies are/have been continuously adding species to the humanity’s portfolio of useful plants; (b) animals have been aiding in this processes in different ways; and, (c) how human–animal–plant relationships unfold in the present could have been similar in the past, thus analogies may be proposed for explaining prehistoric multispecies interactions and their outcomes. With our review, we intend to bring more attention to contemporary pastoralists as plant managers, animals as agents in human-plant interactions, and domestication as a behavioral complex and multispecies process that is as important in the present or future as it was in the past. Our understanding of food production practices is not only fundamental for improving our current frameworks of governance, conservation, and restoration of useful species populations, but also of biocultural diversity altogether.